2021
DOI: 10.1002/pad.1964
|View full text |Cite
|
Sign up to set email alerts
|

Welfare state and the social economy in compressed development: Self‐sufficiency organizations in South Korea

Abstract: Current studies tend to theorize the relationship between the social economy (SE) and social policy based on the experiences of Western welfare states, missing the evolution of social economy organizations (SEOs) in later developing, transitional welfare states. This article fills this gap by examining self-sufficiency organizations in South Korea, which originated from urban SEOs but became agents for microbusiness start-ups under the newly introduced universalistic public assistance scheme. To explain thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…This aligns with a “welfare-to-work” (or “workfare”) institutional logic, which connects welfare to self-help and self-sufficiency, consistent with the layered legacy – or “palimpsest” – of Korea’s “developmental state” (Jeong, 2015, 2017; Lim, 2021). Lim (2021) describes the Korean state as a “workfare state”, reluctant to increase welfare expenditures. Instead, it relies on private organizations, including GCSEs and for-profit companies, to achieve welfare objectives efficiently.…”
Section: Literature Reviewsupporting
confidence: 64%
See 2 more Smart Citations
“…This aligns with a “welfare-to-work” (or “workfare”) institutional logic, which connects welfare to self-help and self-sufficiency, consistent with the layered legacy – or “palimpsest” – of Korea’s “developmental state” (Jeong, 2015, 2017; Lim, 2021). Lim (2021) describes the Korean state as a “workfare state”, reluctant to increase welfare expenditures. Instead, it relies on private organizations, including GCSEs and for-profit companies, to achieve welfare objectives efficiently.…”
Section: Literature Reviewsupporting
confidence: 64%
“…Dart (2004), Yi (2023b) observed that the "moral legitimacy" of SEs, emerging from the neoconservative, neoliberal climates of the 1980s and 1990s in the UK and the USA, was due to their entrepreneurial orientation and capacity for profit generation, distinguishing them from government-dependent welfare organizations. A similar preference for self-sustainable, prosocial, business-like entities informed the Korean public sector's promotion of SEs (Jang, 2017;Lim, 2021;Lim and Endo, 2016;Yi, 2023a). Our findings indicate that while adherence to the EMES economic and entrepreneurial dimensionwhich encapsulates this notionvaries considerably among GCSEs, there is a strong resonance with the framework's social dimension.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation